2020
DOI: 10.15282/ijame.17.1.2020.08.0563
|View full text |Cite
|
Sign up to set email alerts
|

An Aerodynamic Assessment of Vehicle-Side Wall Interaction using Numerical Simulations

Abstract: The effects of induced pressure loads from a realistic vehicle onto the surface of a road-side wall are numerically investigated. Parameters such as vehicle speeds, vehicle-wall separation distances and the effects of inclined walls are examined to numerically characterize the vehicle-wall interactions. Aerodynamic characteristics such as the drag, lift, side forces and pressure coefficients are analyzed on the vehicle to provide a basis for comparison between each of the aforementioned variations. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Trường hợp khích thước miền không gian tính toán quá lớn sẽ ảnh hưởng đến chi phí và thời gian tính toán. Từ các nghiên cứu [11,12,14], tác giả xây dựng miền không gian mô phỏng với các kích thước được mô tả trong hình 4.…”
Section: Miền Không Gian Tín Toánunclassified
“…Trường hợp khích thước miền không gian tính toán quá lớn sẽ ảnh hưởng đến chi phí và thời gian tính toán. Từ các nghiên cứu [11,12,14], tác giả xây dựng miền không gian mô phỏng với các kích thước được mô tả trong hình 4.…”
Section: Miền Không Gian Tín Toánunclassified
“…It must be highlighted that the application of 2D-URANS simulations has inherent limitations in predictive accuracy when addressing the separated reverse fow problem within high Reynolds number fows. Tis defciency persists even within the framework of three-dimensional fow simulations that meticulously account for turbulent anisotropy [22,23]. In the context of a multiple-cylinder array in a heat exchanger, the fow separation on the cylinder surface is notably infuenced by the arrangement of surrounding cylinders, involving interference from adjacent cylinders' structures and separated fows.…”
Section: Simulation Of the Tube Bundle Aerodynamic Noisementioning
confidence: 99%
“…The commonly used RANS approaches are based on Eddy viscosity model, which are widely used in evaluating flow around bluff bodies. Most of the RANS approaches can predict large flow features accurately as shown by Ashton and Revell (2015), Ashton et al (2016), Read and Viswanathan (2020) and Guilmineau et al (2008Guilmineau et al ( , 2011 but for specific RANS approaches, the accuracy is shown to decrease when predicting the base pressure and aerodynamic characteristics such as drag and lift during situations where the adverse pressure gradients and separated flows are present when compared to experimental studies (Guilmineau, 2008;Han, 1989;Khalighi et al, 2001;Murakami, 1993;Rodi, 1997). LES methods are commonly adopted to overcome the aforementioned inaccuracies.…”
Section: Turbulence Modelling Strategiesmentioning
confidence: 99%